Copper production in Majdanpek in sixties and seventies of the 16th century - Katić S.; Ilić I.; Živković D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this paper the practice of mine Majdanpek during sixties and seventies of the XVI century has been investigated with an accent on copper production. The attention has been also given to various subjects from considering copper treatment and use to forbidden activities connected to copper illegal production and trade with Persia.